Possibilities of Using Cognitive and Metacognitive Strategies in The Learning Process - Boymanov Hashim Isroilovich (Researchparks Publishing, 2026)
This article studies the integrated role of cognitive and metacognitive strategies in increasing the effectiveness of independent learning activities. The interaction of these strategies in developing students' ability to self-manage the learning process and the methodology of their practical application are studied. The results of the study show that the integration of cognitive and metacognitive strategies raises students' independent learning activities to a qualitatively new level.